The efficiency of the glass and marble mortar and pestle on the trituration of amalgam - Obana, Thelmarie Allas; Uy, Mary Ann C.
Amalgam samples were made from four kinds of mortars and pestles: namely, glass pestle and mortar (with and without raised center) and marble pestle and mortar (with and without raised center). Those mixed from the amalgamator will serve as control. The samples were stored for 7 days and polished before etching with the iodine etch. These were examined under the stereomicroscope and the different phases are counted using a grid. Even though there is no significant different between the different mortars and pestles, the glass mortar with the raised center had the highest efficiency (next to the amalgamator) while the marble mortar with the raised center has the lowest efficiency.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental amalgams